(untitled) (Mongolian Journal of Chemistry, 2023)
Calculations using density functional theory (DFT) and Monte Carlo methods were performed on 2-methylbenzimidazole, 2-mercaptobenzimidazole, 2-aminobenzimidazole, benzotriazole, and benzimidazole to determine their corrosion inhibition efficiency. The molecular structure was optimized geometrically using DFT calculations at the B3LYP/6– 311 G++(d,p) and b2plypd3/aug-cc-pvdz basis set level in protonated and non-protonated species in gas and water. In this study, HOMO, LUMO, bandgap, ionization energy, electronegativity, hardness, softness, electrophilicity and nucleophilicity, electron transfer, back donation energy and condensed Fukui indices are used to assess a molecule’s local reactivity. Theoretical investigations can precisely establish the geometrical dimensions of a molecule and correctly explain the quantum properties of inhibitors. The mechanism of interaction between inhibitors and metal surfaces in a specified molecule is studied using molecular dynamics. The benzimidazole functional groups absorbed energy linearly on metal surfaces, with quantum characteristics determined using density functional theory and an ab initio technique. Importantly, the findings of this conceptual model are consistent with the corrosion inhibition efficiency of earlier experimental investigations.